Penerapan Problem Based Learning Dengan Eksperimen Untuk Meningkatkan Minat Belajar Ipa Pada Materi Campuran Di Kelas Viii Smpn 2 Sumber - Nurul Waqidah; Nurwanti Fatnah; Teti Herawati (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2025)
This classroom action research (CAR) aimed to enhance students' learning interest through the implementation of the Problem Based Learning(PBL) model combined with experimental methods on the topic of mixture separation methods in class VIII H of SMPN 2 Sumber. The research was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. Data were collected through observation, learning interest questionnaires, and student interviews. The questionnaire results showed an increase in learning interest from 0.58% in the pre-action stage, to 0.70% in the first cycle, and further to 0.84% in the second cycle. This improvement was supported by observations and interviews indicating increased student engagement and understanding. Based on these findings, it can be concluded that the application of the PBL model with experimental activities effectively enhances students’ interest in science learning.